A Two-Relaxation-Time Lattice Boltzmann Model for Electron Beam Selective Melting Additive Manufacturing - Chen, Daoliang; Chen, Wei; Liu, Yanfei; Sun, Dongke (Frontiers in Materials, 2022)
Electron beam selective melting is a rapidly developing additive manufacturing technology for industry and engineering. A two-relaxation-time lattice Boltzmann model is proposed to simulate melt flows and free surface dynamics in an EBSM additive manufacturing process. The model also describes the dynamics of solid-liquid phase change and heat transfer, and it is validated by several simulations of classical benchmarks. The model was applied to further simulate single and multiple tracks of electron beam selective melting on a single layer of powder bed and to analyze the influence of process parameters. The results demonstrate significant potentials of the present model for the study of additive manufacturing processes.